Electrohydrodynamic Stability of Poorly Conducting Parallel Plasma Flows - Shubha, N (AIP conference proceedings, 2006)
Aerospace, automobile, structural and biomedical engineering applications require strong and smart materials to minimize the weight and vibrations and maximize the strength to achieve an efficient dynamic response and economic advantages. These materials are usually synthesized using poorly conducting plasma in the presence of a strong electric field. This strong applied electric field produces instabilities known as Electrohydrodynamic instability in a poorly conducting parallel flow of plasma. These instabilities produce impurities in the manufacture of strong smart materials. Therefore to manufacture these materials free from impurities there is a need to know whether this external constraint of electric field either suppress or augments these electrohydrodynamic instabilities. This can be achieved by investigating Electrohydrodynamic stability in the presence of an external constraint of strong electric field. The study of this instability is the main objective of this paper. In this paper, stability of poorly conducting parallel plasma in a rectangular channel is studied in the presence of strong electric field subject to linear stability analysis. The basic flow is a function of electric potential and we found that this potential difference also drives the flow in addition to plasma pressure gradient. The condition for the onset of stability is determined in terms of Electric Reynolds Number using both moment and energy methods combined with Galerkin technique. If the motion is unstable an upperbound for the amplification factor is given. From this analysis we conclude that a proper choice of Electric Reynolds number controls instability of a parallel poorly conducting plasma. This result is useful in the manufacture of strong and smart materials free from impurities.